Just multiply the stuff together, FOIL-style.
(3+4i)(2-i)
6 -3i +8i -4i^2
6 + 5i -4*(-1)
6+5i +4
10 + 5i
There, not so hard, is it? :-)
2007-03-21 17:01:46
·
answer #1
·
answered by Bramblyspam 7
·
0⤊
0⤋
Multiplying complex numbers is just the same as multiplying an expression.
Just like the way you do:
(x+3)(y-4)
You use the FOIL method.
(3 +4i) (2- i)
Multiply the FIRST TERM:
(3)(2)
Multiply the OUTER TERM:
(3)(-i)
Multiply the INNER TERM:
(4i)(2)
Multiply the LAST TERM:
(4i)(-i)
Then adding all these terms, gives:
6 - 3i +8i - 4i^2
combine similar terms:
6 + 5i -4i^2
For the imaginary number i, we know that:
i=sq.root(-1)
so, i^2 means:
sq.root(-1)^2
since the square root and the squared cancels each others effect:
i^2= -1
substituting this to the equation gives:
6 + 5i -4(-1)
6 +5i +4
combining similar terms, gives the final answer:
10 + 5i
2007-03-22 00:13:39
·
answer #2
·
answered by activista 2
·
0⤊
0⤋
Note that i² = - 1
(3 + 4i).(2 - i) = 6 - 3i + 8i - 4i² = 6 + 5i + 4 = 10 + 5i
2007-03-22 06:36:19
·
answer #3
·
answered by Como 7
·
0⤊
0⤋
(3 + 4i)(2 - i)
This works the same as multiplying two binomials such as 4x+1 and 5x-8
(4x + 1)(5x - 8) = (4x)(5x) + (4x)(-8) + (1)(5x) + (1)(-8)
= 20x^2 - 32x + 5x - 8
=20x^2 - 27x - 8
The only difference is that with i, because of the definition of i, you replace i with -1 and continue to simplify.
So, as an example:
(7 + 3i)(2 - 4i) = (7)(2) + (7)(-4i) + (3i)(2) + (3i)(-4i)
= 14 - 28i + 6i -12i^2
= 14 - 22i -12(-1), since by definition i^2 = -1
= 14 - 22i + 12
= 26 - 22i
As a math teacher, I have a difficult time just giving an answer. I hope this helps you understand so you can do any other problem like this.
2007-03-22 00:07:48
·
answer #4
·
answered by polymac98 2
·
0⤊
0⤋
(3+4i)(2-i)
use the foil.
=6+5i-4i^2
remember that i^2=-1
=6+5i-4(-1)
=6+5i+4
=10+5i answer
2007-03-22 00:10:24
·
answer #5
·
answered by Engr. Ronald 7
·
0⤊
0⤋
(3 + 4i)(2 - i)
First, FOIL it out.
6 - 3i + 8i - 4i^2
Remember though that i^2 = -1.
6 - 3i + 8i - 4(-1)
Simplify and group like terms.
6 + 5i + 5
11 + 5i
2007-03-22 00:01:14
·
answer #6
·
answered by Puggy 7
·
0⤊
1⤋
Factor it out..or multiply..whatever the word is...i'll say expand
6+8i-3i-4i^2
i = square root of -1
so i^2 = -1....
square root of 2 * square root of 2 = 2
so square root of -1 * square root of -1 = -1
6+5i-4(-1)
6+4+5i
10+5i
2007-03-22 00:02:47
·
answer #7
·
answered by My name is not bruce 7
·
0⤊
1⤋
10+5i
2007-03-22 00:02:15
·
answer #8
·
answered by lisandrogutierrez 1
·
0⤊
0⤋